Are routine post drain removal chest x-rays necessary after oesophagectomy? - Aboul-Enein, Mohamed Saad; Knight, William R. C.; Foley, Daniel; McKnickle, Luke; Carter, Harrison; Gossage, James A. (International Surgery Journal, 2020)
Background: Routine chest X-rays (CXR) are often performed following the removal of chest drains placed during oesophagectomy. CXRs are costly and inconvenient for the patient, often being performed out of working hours. The aim of this study was to evaluate whether routine CXR is necessary following drain removal or if CXRs should only be performed when indicated by the clinical status of the patient. Methods: This was a retrospective study of oesophagectomies performed at a single high volume centre. Routine post chest drain removal CXRs were analyzed and compared to baseline post-operative CXRs. The clinical status of the patient before and after chest drain removal was recorded. Results: 188 patients were identified. 111/188 (59%) had a pleural effusion or pneumothorax on their baseline post-operative CXR. Abnormal findings on post drain removal CXR were common with 72/188 (38.3%) patients having a new or worse pleural effusion or pneumothorax. Only, 5.6% (11/188) of these patients actually developed clinical signs after chest drain removal. Of these, only 2.1% (4/188) required chest drain re-insertion. No patients underwent intervention without showing clinical deterioration. No re-intervention was prompted by CXR finding alone. Conclusions: Routine CXR following chest drain removal is unnecessary. It is safe to only perform CXRs on patients who develop clinical signs.